Response Differences Between Ectocarpus Siliculosus Populations to Copper Stress Involve Cellular Exclusion and Induction of the Phytochelatin Biosynthetic Pathway - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
Some populations of brown seaweed species inhabit metal-polluted environments and can develop tolerance to metal stress, but the mechanisms by which this is accomplished are still to be elucidated. To address this, the responses of two strains of the model brown alga Ectocarpus siliculosus isolated from sites with different histories of metal contamination exposed to total copper (CUT) concentrations ranging between 0 and 2.4 mu M for 10 days were investigated. The synthesis of the metal-chelator phytochelatin (PCs) and relative levels of transcripts encoding the enzymes gamma-glutamylcysteine synthetase (gamma-GCS), glutathione synthase (GS) and phytochelatin synthase (PCS) that participate in the PC biosynthetic pathway were measured, along with the effects on growth, and adsorption and uptake of Cu. Growth of strain LIA, from a pristine site in Scotland, was inhibited to a greater extent, and at lower concentrations, than that of Es524, isolated from a Cu-contaminated site in Chile. Concentrations of intra-cellular Cu were higher and the exchangeable fraction was lower in LIA than Es524, especially at the highest exposure levels. Total glutathione concentrations increased in both strains with Cu exposure, whereas total PCs levels were higher in Es524 than LIA; PC2 and PC3 were detected in Es524 but PC2 only was found in LIA. The greater production and levels of polymerisation of PCs in Es524 can be explained by the up-regulation of genes encoding for key enzymes involved in the synthesis of PCs. In Es524 there was an increase in the transcripts of -gamma-GCS, GS and PCS, particularly under high Cu exposure, whereas in LIA4 transcripts of gamma-GCS1 increased only slightly, gamma-GCS2 and GS decreased and PCS did not change. The consequences of higher intra-cellular concentrations of Cu, lower production of PCs, and lower expression of enzymes involved in GSH-PCs synthesis may be contributing to an induced oxidative stress condition in LIA, which explains, at least in part, the observed sensitivity of LIA to Cu. Therefore, responses to Cu exposure in E. siliculosus relate to the contamination histories of the locations from where the strains were isolated and differences in Cu exclusion and PCs production are in part responsible for the development of intra-specific resistance. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ectoconpus siliculosus; Brown algae; Copper; Phytochelatins; Glutathione; Inter-population variation